Asian patients' perspectives on advance care planning: A mixed-method systematic review and conceptual framework. (December 2021) - Martina, Diah; Geerse, Olaf P; Lin, Cheng-Pei; Kristanti, Martina S; Bramer, Wichor M; Mori, Masanori; Korfage, Ida J; van der Heide, Agnes; Rietjens, Judith AC; van der Rijt, Carin CD
Background: Asian healthcare professionals hold that patients' families play an essential role in advance care planning. Aim: To systematically synthesize evidence regarding Asian patients' perspectives on advance care planning and their underlying motives. Design: Mixed-method systematic review and the development of a conceptual framework (PROSPERO: CRD42018099980). Data sources: EMBASE, MEDLINE, Web of Science, and Google Scholar were searched for studies published until July 27, 2020. We included studies concerning seriously-ill Asian patients' perspectives on advance care planning or their underlying motives for engaging or not engaging in it. Results: Thirty-six articles were included; 22 were quantitative and 27 were from high-income countries. Thirty-nine to ninety percent of Asian patients were willing to engage in advance care planning. Our framework highlighted that this willingness was influenced not only by their knowledge of their disease and of advance care planning, but also by their beliefs regarding: (1) its consequences; (2) whether its concept was in accordance with their faith and their families' or physicians' wishes; and (3) the presence of its barriers. Essential considerations of patients' engagement were their preferences: (1) for being actively engaged or, alternatively, for delegating autonomy to others; (2) the timing, and (3) whether or not the conversations would be documented. Conclusion: The essential first step to engaging patients in advance care planning is to educate them on it and on their diseases. Asian patients' various beliefs about advance care planning should be accommodated, especially their preferences regarding their role in it, its timing, and its documentation.